Psychopathy and violence in criminals - Serin, R. C. (Journal of interpersonal violence, 1991)
The present study investigated the relationship between criminal psychopathy and violent behavior. Groups were defined according to psychopathy ratings (Hare's Psychopathy Checklist) and violence. Psychopaths scored higher than nonpsychopaths on measures of impulsiveness and aggressiveness, and they were more likely than other inmates to behave aggressively, to have committed more serious past offenses, to have used weapons, threats and instrumental aggression, and to have suffered physical abuse as a child. When presented with hypothetical situations that involved a frustrating outcome, psychopaths reported that they would be more angry than nonpsychopaths, and they attributed greater hostile intent to others. Violent psychopaths were seen as qualitatively different than violent nonpsychopaths in their use of violence, yet they did not differ in terms of the seriousness of their index offense